IMPLEMENTASI KERJASAMA RUANG SIBER ANTARA INDONESIA DAN AMERIKA SERIKAT DALAM MENINGKATKAN KAPASITAS PENANGANAN ANCAMAN CYBERTERRORISM DI INDONESIA - Bimo Arya Putra (2022)
The development of technology and the increasing use of the internet has increasingly made the dominance of the cyber world in all international issues inseparable. The cyber world itself is a relatively new concept, with a very minimal international regulations on how a country should act in this domain. Realizing this, many countries in the world are starting to make many strategies and plans in capitalizing the cyber world for their benefit but some still need to survive. To deal with this, many countries have begun to cooperate in an effort to increase their capabilities in the massive cyber world, this not only provides many opportunities for development but also creates many new threats such as hacktivism, cyberspies, cyberterrorism. With the urgency that exists, Indonesia has begun to initiate cooperation with various countries on cyber issues, including with the superior country the United States in the agreement regulated by the Letter of Intent. The author has identified cyberterrorism as one of the threats that needs to be analyzed due to its large threat to Indonesia. By examining the LoI, the author has concluded that being led by the BSSN, there are 2 important aspects in dealing with cyberterrorism, namely capacity building and information sharing. Although these two things have been done, the impact has not significantly developed Indonesia's cybersecurity due to the lack of intense and effective implementation of the two programs